Perlindungan Konsumen terhadap Barang yang Diberikan oleh Jasa Pengiriman Barang Melalui Asuransi (Studi pada PT. Tikijalur Nugraha Eka Kurir Cabang Danau Poso Sanur) - Dhania Bagus Fajar Trianti; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
In the rapidly developing world, many changes have occurred, especially in the fields of development and the economy. In particular, companies that provide goods delivery services, one of which is PT. Tiki Lane Nugraha Ekakurir Lake Poso Sanur Branch. The relationship in this goods delivery agreement creates rights and obligations for both parties involved, hereinafter referred to as a legal relationship. There are two problem formulations in this study, namely, How is the responsibility of PT. Tiki Lintas Nugraha Ekakurir, Danau Poso Sanur Branch for the loss or damage of goods to insured goods shipments? And what are the procedures for claiming insurance for loss or damage to goods at PT. Tiki Lane Nugraha Ekakurir Lake Poso Sanur Branch?. This study uses empirical research methods. With the discussion that PT. Tiki Jalur Nugraha Ekakurir, Danau Poso Sanur Branch, has established insurance for goods, and the procedure for claiming is with the victim visiting the office where the transaction was made. However, if the party providing the insurance is not responsible for its obligation to provide insurance, then the administrative sanction as stated in Article 60 of the UUPK, and Article 1999 of the UULAJ may be imposed.